The Shifting of Special Education Orthodoxy in Implementing Inclusive Education Policies in Indonesia - Suprihatiningrum, Jamil; Astuti, Mawar Rahayuning; Saputri, Legendaria Raula (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to portray the implementation of inclusive education policies organized by two different educational institutions for students with disabilities, namely Special School Angkasa Lambeyan and Primary School Bintang Poncol in Magetan Jawa Timur. A qualitative multiple case study was selected as the research method by involving school principals, support teachers, and student guardians as participants. Data were collected through unstructured interviews, observation, and analysis of policy documents implemented by the two schools. All data collected from the two cases were analyzed using an explanation technique and the credibility of the data was guaranteed through method triangulation techniques. The results of this study showed that the implementation of inclusive education policies in each school positively impacts the ability of students with disabilities Â to obtain an equal education. The readiness of those schools to implement inclusive education programs is also reflected in this study. Communication, interaction, and collaboration between local governments and educational institutions need to be improved to guarantee and realize accessibility for inclusive education.